To determine which expression is equal to \(5.1 \times 10^{-3}\), we need to evaluate the responses one by one:
-
\(2.9 \times 10^{-3} + 1.2 \times 10^{-3}\) \[ 2.9 \times 10^{-3} + 1.2 \times 10^{-3} = (2.9 + 1.2) \times 10^{-3} = 4.1 \times 10^{-3} \quad \text{(not equal)} \]
-
\(3.5 \times 10^{3} + 1.6 \times 10^{-6}\) \[ 3.5 \times 10^{3} + 1.6 \times 10^{-6} \quad \text{(not equal, as one is positive exponent and the other is negative)} \]
-
\(3.9 \times 10^{-3} + 1.2 \times 10^{-3}\) \[ 3.9 \times 10^{-3} + 1.2 \times 10^{-3} = (3.9 + 1.2) \times 10^{-3} = 5.1 \times 10^{-3} \quad \text{(equal)} \]
-
\(2.2 \times 10^{-1} + 2.9 \times 10^{-2}\) Let's convert \(2.2 \times 10^{-1}\) to the same exponent: \[ 2.2 \times 10^{-1} = 22 \times 10^{-2} \] Now, \[ 22 \times 10^{-2} + 2.9 \times 10^{-2} = (22 + 2.9) \times 10^{-2} = 24.9 \times 10^{-2} \] Converting this back to a power of \(10^{-3}\): \[ 24.9 \times 10^{-2} = 249 \times 10^{-3} \quad \text{(not equal)} \]
From the evaluations, we see that the correct response is:
3.9×10−3 + 1.2×10−3